Jobs, Crime and Votes: A Short‐run Evaluation of the Refugee Crisis in Germany. (23rd March 2022) - Gehrsitz, Markus; Ungerer, Martin
Abstract : Millions of refugees made their way to Europe between 2014 and 2015, with over one million arriving in Germany alone. Yet little is known about the impact of this inflow on labour markets, crime and voting behaviour. This paper uses administrative data on asylum seeker allocation and provides an evaluation of the short‐run consequences of the refugee inflow. Our identification strategy exploits the fact that a scramble for accommodation determined the assignment of asylum seekers to German counties, resulting in exogenous variation in the number of asylum seekers per county within and across states. Our estimates suggest that those migrants have not displaced native workers but have themselves struggled to find gainful employment. We find moderate increases in crime, and our analysis further indicates that while at the macro level increased migration was accompanied by increased support for anti‐immigrant parties, exposure to asylum seekers at the micro level had a small negative effect.